2021
DOI: 10.3390/catal11080971
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst and Elemental Analysis Involving Biodiesel from Various Feedstocks

Abstract: The world is currently faced with the depletion of fossil fuel energy sources and their use is associated with environmental pollution. This has triggered the need to seek alternative energy sources that are renewable, sustainable and environmentally benign. Biodiesel, an alternative fuel of interest, is obtainable from biomass feedstocks. In existing biodiesel fuel, there are concerns that it is a contaminant due to its elemental contents, which over time also affect its quality. This study aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Table 8 compares the trace metal levels in biodiesel produced from waste sunflower oil (Simbi et al 2021 ), waste palm oil (Simbi et al 2021 ), waste cooking oil (Park et al 2019 ), and waste canola oil (Hossain et al 2010 ) from the literature with those reported in this study. As shown in this table, trace metal levels from the literature are comparable with those found in biodiesels produced from heated canola oils at 190 and 240 °C.…”
Section: Ft-ir Analysis Of Biodiesel and Bioglycerolmentioning
confidence: 85%
“…Table 8 compares the trace metal levels in biodiesel produced from waste sunflower oil (Simbi et al 2021 ), waste palm oil (Simbi et al 2021 ), waste cooking oil (Park et al 2019 ), and waste canola oil (Hossain et al 2010 ) from the literature with those reported in this study. As shown in this table, trace metal levels from the literature are comparable with those found in biodiesels produced from heated canola oils at 190 and 240 °C.…”
Section: Ft-ir Analysis Of Biodiesel and Bioglycerolmentioning
confidence: 85%